Effect of Titanium Dioxide Film Thickness on Photocatalytic and Bactericidal Activities Against Listeria monocytogenes. (11th February 2019) - Barthomeuf, Marion; Castel, Xavier; Le Gendre, Laurent; Louis, Justine; Denis, Martine; Pissavin, Christine
Abstract: Structural, microstructural and bactericidal surface properties of TiO2 ‐coated glass substrates elaborated by reactive Radiofrequency sputtering are investigated. As pathogenic bacteria in biofilms are a major concern in food industries due to their growing resistance to cleaning and sanitizing procedures, the development of photoactive surfaces exhibiting bactericidal properties is acknowledged as an effective approach to tackle bacterial contaminations. Our principal aim concerns the study of the photoactive top‐layer thickness impact (from 80 nm to 500 nm) on Listeria monocytogenes . Structural characterization of the TiO2 layers demonstrates that anatase and rutile phases are both present, depending on the film thickness. Photocatalytic activity of the samples has been evaluated through the degradation of aqueous methylene blue (MB) solutions under UVA light illumination for various time periods. The results show an efficiency rating increase according to TiO2 film thickness up to a threshold value close to 400 nm. Moreover, a significant decrease of the adherent bacteria number is observed after 20 min of UVA illumination. The quantitative study of the bactericidal activity associated with scanning electron microscopy observations of the postprocess bacteria damaged cells demonstrates the efficiency of the 240‐nm‐thick TiO2 coating sample. The results are correlated with the production of hydroxyl radicals during the process of photocatalysis. Abstract : The photocatalytic activity of TiO2 thin layers increases according to TiO2 film thickness to a threshold value close to 400 nm. The film thickness also influences positively the antibacterial activity even though the two strains of Listeria monocytogenes (Lm ScottA and Lm ECL 136) showed different sensitivity to TiO2 photocatalysis.